The complete mitochondrial genome of Eremias przewalskii (Squamata: Lacertidae). (3rd May 2016) - Du, Yu; Qiu, Qing-Bo; Tong, Qing-Lin; Lin, Long-Hui
Abstract: In this paper, the complete mitochondrial genome of Eremias przewalskii (Squamata: Lacertidae) is reported, which is a circular molecule of 18, 225 bp in size. The base composition of mtDNA is as follows: 30.3% A, 27.9% T, 27.9% C and 13.9% G. The genome consists of 13 protein coding genes, 22 transfer RNAs, 2 ribosomal RNA genes and one putative control region.